Fused diethynylbenzenes and phenanthrenes via arynes with alkynylsilanes. Issue 13 (25th January 2023) - Dong, Jie; Lei, Yu; Hu, Qiong; Zong, Lingli; Zhang, Ke; Zhang, Yajuan; Hu, Yimin
Abstract : The concept of organosilicon in organic synthesis is applied to the hydroalkynylation and base promoted intramolecular cyclization reactions of hexadehydro-Diels–Alder-derived benzynes. Abstract : A method for the hydroalkynylation and catalytic cyclization reactions of hexadehydro-Diels–Alder-derived benzynes is described. Diethynylbenzene derivatives are generated in a one-step reaction via trimethylsilyl-alkyne groups with benzyne formed by heating the appropriate tetrayne substrate. Trimethyl(phenylethynyl)silane loses TMS and binds to the electron-deficient site on HDDA-derived benzynes, and then phenanthrene was synthesized under mild reaction conditions by transition-metal-free, base promoted intramolecular cyclization.